The nature and purpose of liberal education - Nicgorski, Walter (Universidad Panamericana, Instituto de Humanidades, 2021)
This is the first of three lectures on the theme of Liberal Education and Human Freedom presented late in 2017 as a master class in Catedra Carlos Llano. The lectures were given at Universidad Panamericana’s campuses at Aguascalientes and Mexico City on successive weeks.
Keywords: Liberal education; Virtue; Thomism; University; Cátedra Carlos Llano; Conocimiento y Acción - Revista de Humanidades; HUMANIDADES Y CIENCIAS DE LA CONDUCTA